2016
DOI: 10.1038/ni.3580
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a role for TRIM29 in the control of innate immunity in the respiratory tract

Abstract: The respiratory tract is heavily populated with innate immune cells, but the mechanisms that control such cells are poorly defined. Here we found that the E3 ubiquitin ligase TRIM29 was a selective regulator of the activation of alveolar macrophages, the expression of type I interferons and the production of proinflammatory cytokines in the lungs. We found that deletion of TRIM29 enhanced macrophage production of type I interferons and protected mice from infection with influenza virus, while challenge of Trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(162 citation statements)
references
References 49 publications
2
155
2
Order By: Relevance
“…Vero cells were infected with VSV supernatants for 1 h at room temperature as described [41]. After washing with PBS, the plate was overlaid with Dulbecco’s modified Eagle medium containing 1% low melting-point agarose and incubate at 37 °C for 24 h before crystal violet staining.…”
Section: Methodsmentioning
confidence: 99%
“…Vero cells were infected with VSV supernatants for 1 h at room temperature as described [41]. After washing with PBS, the plate was overlaid with Dulbecco’s modified Eagle medium containing 1% low melting-point agarose and incubate at 37 °C for 24 h before crystal violet staining.…”
Section: Methodsmentioning
confidence: 99%
“…80,81 E3 ligase TRIM29 inhibits IRF3 signaling via the transcription factor NF-κB by directing binding to NEMO and inducing its ubiquitination and proteolytic degradation. 82 In addition, sumoylation contributes to repression of both inflammatory and antiviral responses, partially via targeting and suppressing activity of the Ifnb1 promoter. 83 These data identify key negative regulators of innate immunity and might have important clinical implications for related inflammatory and infectious diseases.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…Our previous studies have shown that GIT1 can interact with certain proteins, such as ASK1, ERK1/2, and sorting nexin‐6, via similar CC structures between them. A recent study has reported that NEMO binds to the E3 ubiquitin ligase TRIM29, inducing NEMO degradation via the CC domain in TRIM29 . Therefore, we predicted that GIT1 would bind to NEMO via the CC domain of each protein.…”
Section: Resultsmentioning
confidence: 92%